Ex vitro propagation and phytochemical analysis of Serapias vomeracea (Burm.f.) Briq.: contribution to the conservation of Orchidaceae species - Esin Çolak; Erdi C. Aytar; Yasemin Ö. Kömpe (Spanish Journal of Agricultural Research)
Aim of study: The primary objective of this study was to investigate the seed germination and antioxidant propertiesof Serapias vomeracea (Burm.f.) Briq. Specifically, the aims of the research were to explore the influence of the Tulasnellaceae spp, fungal isolate SVL-30 (MK250656), on germination and seedling development, compare antioxidant activity to that of ascorbic acid, analyse the phytochemical composition, and identify bioactive compounds present in the methanol extract.